A critical assessment of brazil’s emerging pharmaceutical market - Palmer, Jiibril (2016)
Brazil has emerged as a leader in new sites selected for clinical trials, by offering a multitude of benefits to sponsors. Even though there are significant delays with regulatory timelines, it provides highly qualified investigators, low costs, a strong infrastructure, well-established ethical support, and high patient recruitment and adherence rates. However, in order to become a primary location for clinical trials, Brazil will have to streamline and improve regulatory processes and the current political and financial conditions. The study was conducted with consensus judgement and analysis of 15 experienced industry reviewers have provided informative descriptive data. The findings suggest areas in new clinical trial in which strategies for workflow and process development could improve efficiency of clinical development.